Prognostic relevance of pulmonary arterial compliance after therapy initiation or escalation in patients with pulmonary arterial hypertension. (1st March 2017) - Ghio, Stefano; D'Alto, Michele; Badagliacca, Roberto; Vitulo, Patrizio; Argiento, Paola; Mulè, Massimiliano; Tuzzolino, Fabio; Scelsi, Laura; Romeo, Emanuele; Raineri, Claudia; Martino, Lavinia; Tamburino, Corrado; et al.
Abstract: Background: Conventional hemodynamic parameters are considered to be the gold standard indices of outcome in pulmonary arterial hypertension (PAH); on the contrary, few data support the hypothesis that the pulsatile component of right ventricular afterload provides important prognostic information. The aim of the study was to investigate the prognostic significance of pulmonary arterial compliance (PCa) after therapy initiation or escalation in PAH patients. Methods: A cohort of 419 consecutive PAH patients (308 naive and 111 prevalent) underwent right heart catheterisation (RHC) prior to initiating or escalating PAH-targeted therapy. RHC was repeated in 255 patients (61%) after 4 to 12 months of therapy as 62 patients (15%) died and 102 (24%) did not undergo a follow-up RHC within the first year. Results: After the follow-up RHC, 63 patients died over a median follow-up period of 39 months. At multivariate analysis, age > 50 years old, male gender, etiology associated with systemic sclerosis, persistence of WHO class III/IV, and reduced PCa at follow-up RHC were the independent parameters significantly associated with poor prognosis. At ROC analysis, the optimal cut-off point of PCa to predict survival was 1.4 mL/mmHg (AUC 0.73, sensitivity 81.8%, specificity 58.8%). Conclusions: In PAH patients hospitalized to initiate or to escalate PAH-specific therapy, failure to improve PCa after therapy is a strong hemodynamic predictor of poor prognosis.